Early Life Adversity as a Risk Factor for Visceral Pain in Later Life: Importance of Sex Differences - Chaloner, Aaron; Greenwood-VanMeerveld, Beverley (Frontiers in Neuroscience, 2013)
A history of early life adversity (ELA) has health-related consequences that persist beyond the initial maltreatment and into adulthood. Childhood adversity is associated with abnormal glucocorticoid signaling within the hypothalamic-pituitary-adrenal (HPA) axis and the development of functional pain disorders such as the irritable bowel syndrome (IBS). IBS and many adult psychopathologies are more frequently diagnosed in women, and ovarian hormones have been shown to modulate pain sensitivity. Therefore, the sexually dimorphic effects of ELA and the role of ovarian hormones in visceral pain perception represent critical research concepts to enhance our understanding of the etiology of IBS. In this review, we discuss current animal models of ELA and the potential mechanisms through which ovarian hormones modulate the HPA axis to alter nociceptive signaling pathways and induce functionally relevant changes in pain behaviors following ELA.